Risk Factors for Postpartum Maternal Infection Following Spontaneous Vaginal Delivery Complicated by Chorioamnionitis - Helen A. Daifotis; Megan M. Smith; Anna E. Denoble; Sarah K. Dotters-Katz (American Journal of Perinatology Reports, 2020)
Objective Guidelines for the management of chorioamnionitis include intrapartum antibiotics, while postpartum antibiotics after spontaneous vaginal delivery (SVD) are reserved high-risk women. Our objective is to describe the incidence of and risk factors for postpartum infection after SVD complicated by chorioamnionitis. Study Design This is a retrospective study of SVDs with clinically diagnosed chorioamnionitis at a single center. The primary outcome was a composite of postpartum infection. Women who developed the primary outcome were compared with those who did not using bivariate statistics. Regression models were developed to estimate adjusted odds of outcomes. Results In this cohort, 346 women underwent SVD complicated by chorioamnionitis. Of these, 23 (6.6%) developed postpartum infections (endometritis n = 7, urinary tract infection/pyelonephritis n = 6, sepsis n = 4, and perineal wound infection n = 6). Receipt of antibiotics intra- or postpartum did not differ between groups, but women with postpartum infections were more likely to deliver prior to 32 weeks (17.4 vs. 4.9%, p = 0.04). When controlling for antibiotic use, delivery at < 32 weeks was associated with 3.8-fold increased (95% confidence interval: 1.07–13.7) odds of postpartum infection. Conclusion Postpartum infections occur in ∼1/15 women delivering vaginally with chorioamnionitis, with those who deliver at < 32 weeks' gestation being at increased risk.